A lipidomic and metabolomic signature of a very low-carbohydrate high-fat diet and high-intensity interval training: an additional analysis of a randomized controlled clinical trial - Cipryan, Lukas; Kosek, Vit; García, Carlos J; Dostal, Tomas; Bechynska, Kamila; Hajslova, Jana; Hofmann, Peter (Metabolomics, 2023)
INTRODUCTION: Regular physical activity and dietary variety are modifiable and influential factors of health outcomes. However, the cumulative effects of these behaviors are not well understood. Metabolomics may have a promising research potential to extend our knowledge and use it in the attempts to find a long-term and sustainable personalized approach in exercise and diet recommendations. OBJECTIVE: The main aim was to investigate the effect of the 12 week very low carbohydrate high fat (VLCHF) diet and high-intensity interval training (HIIT) on lipidomic and metabolomic profiles in individuals with overweight and obesity. METHODS: The participants (N = 91) were randomly allocated to HIIT (N = 22), VLCHF (N = 25), VLCHF + HIIT (N = 25) or control (N = 19) groups for 12 weeks. Fasting plasma samples were collected before the intervention and after 4, 8 and 12 weeks. The samples were then subjected to untargeted lipidomic and metabolomic analyses using reversed phase ultra-high-performance liquid chromatography coupled to high-resolution mass spectrometry. RESULTS: The VLCHF diet affected plasma lipids considerably while the effect of HIIT was unremarkable. Already after 4 weeks of intervention substantial changes of plasma lipids were found in both VLCHF diet groups. The changes persisted throughout the entire 12 weeks of the VLCHF diet. Specifically, acyl carnitines, plasmalogens, fatty acyl esters of hydroxy fatty acid, sphingomyelin, ceramides, cholesterol esters, fatty acids and 4-hydroxybutyric were identified as lipid families that increased in the VLCHF diet groups whereas lipid families of triglycerides and glycerophospholipids decreased. Additionally, metabolomic analysis showed a decrease of theobromine. CONCLUSIONS: This study deciphers the specific responses to a VLCHF diet, HIIT and their combination by analysing untargeted lipidomic and metabolomic profile. VLCHF diet caused divergent changes of plasma lipids and other metabolites when compared to the exercise and control group which may contribute to a better understanding of metabolic changes and the appraisal of VLCHF diet benefits and harms. CLINICAL TRIAL REGISTRY NUMBER: NCT03934476, registered 1st May 2019 https://clinicaltrials.gov/ct2/show/NCT03934476?term=NCT03934476&draw=2&rank=1 .
Keywords: sacharidy; Diet, High-Fat; dieta s vysokým obsahem tuků; Triglycerides; metabolomika; vysoce intenzivní intervalový trénink; triglyceridy; Humans; lipidomika; lidé; Carbohydrates; Metabolomics; High-Intensity Interval Training; Lipidomics